A Stereospecific Synthesis and Unambiguous Assignment of the Absolute Configuration of (−)‐erythro‐Mefloquine Hydrochloride. Issue 18 (11th December 2013) - Zhou, Gang; Liu, Xian; Liu, Xueying; Nie, Huifang; Zhang, Shengyong; Chen, Weiping
Abstract (−)‐erythro‐Mefloquine hydrochloride was synthesized stereospecifically from commercially available (S)‐(−)‐1‐Boc‐2‐piperidinecarboxylic acid in four steps without disturbing the chiral center, and the absolute configuration of (−)‐erythro‐mefloquine hydrochloride was unambiguously determined as (11R, 12S). (11S, 12R)‐(+)‐erythro‐Mefloquine hydrochloride was synthesized utilizing [(S, S)‐TsDpen]Ru(p‐cymene)Cl complexes‐catalyzed enantioselective transfer hydrogenation of pyridyl ketone 7 as the key step, and the sense of asymmetric induction of 2‐pyridyl ketone 7 is opposite to that of normal ketones in the transfer hydrogenation. Our results confirm the correctness of the determination of the absolute configuration by three physical chemistry methods, and, unbelievably, the erroneous assignments by all previous five asymmetric syntheses. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>